Spatiotemporal Characteristic of Land Use/Land Cover Changes in the Middle and Lower Reaches of Shule River Basin Based on an Intensity Analysis - Fuwen Da (Sustainability, 2019)
The vegetation response to climatic factors is a hot topic in global change research. With the Support of ArcGIS and ENVI software, six sets of Landsat remote sensing images of the middle and lower reaches of the Shule River Basin were interpreted. Eight types of land use and land covers were obtained and the spatiotemporal characteristics of the land use/land cover changes (LUCCs) were analyzed using an intensity analysis to provide a basis for decision-making on the sustainable development of the basin. In the past 29 years, the area of cropland, construction land and shrubland had a net increase, while high-coverage grassland (HCG), medium-coverage grassland (MCG), low-coverage grassland (LCG), wetland and non-vegetation land all presented a net decrease. The area of artificial vegetation (cropland) presented an expanding trend and increased by 1105.56 km2 in total, while the natural vegetation (grassland, shrubland, wetland) showed a shrinking tendency and decreased by 917.69 km2. The intensity analysis revealed that the rate of LUCC in the period of 2000~2006 and 2006~2010 was relatively higher, although the rate of LUCC in other periods was much lower. The change intensities of MCG and HCG were greatest, followed by LCG, shrubland and wetland. Construction land and cropland were in third place, while non-vegetation land was in last place. The pattern of regional LUCC was generally stable except for cropland loss and the gain/loss change of other land-use/land-cover types was always in an active state. For spatial distribution, few changes were observed in the old irrigated area within the oasis. The LUCC was mainly concentrated in the oasis fringe area, natural vegetation cover area and emigrant arrangement regions.